IMPLEMENTASI E-LEARNING DENGAN MODEL PACE BERBANTUAN MODUL BERBASIS MASALAH PADA KONDISI PANDEMIC COVID-19 - Yusfita Yusuf; Hardi Suyitno; Y.L Sukestiyarno; Isnarto Isnarto; Agus Jaenudin (Universitas Cokroaminoto Palopo, 2021)
The Covid-19 pandemic condition prompted the government to recommend study from home, therefore e-learning was used as an alternative implementation of learning. In e-learning it is necessary to set learning objectives, learning models and learning media that are used to deliver teaching materials. Therefore, PACE model using problem-based learning with modules aid is used with the aim of learning statistical reasoning. The purpose of this study was to determine the implementation of e-learning with the PACE model assisted by problem-based modules in statistical lectures in the Covid-19 pandemic condition and the effectiveness of e-learning with the PACE model assisted by problem-based modules in statistical lectures on statistical reasoning. The research method used is a descriptive method with a sample of 24 students who took the research statistics course. The results showed that the implementation of e-learning with PACE model using problem-based learning with modules aid in statistics lectures in the Covid-19 pandemic conditions can be carried out according to the plan, using the google classroom application and whatsapp as learning media. The effectiveness of the learning model on statistical reasoning is proven effective, where the average value of statistical reasoning is 74.58 and the reasoning increase in the medium category is 54%.